High Prices in Samʾal/Yʾdy before Panamuwa II’s Reign - Dušek, Jan (Aramaic studies, 2025)
Bar-Rākib, king of Samʾal/Yʾdy, commissioned an inscribed statue to commemorate his deceased father King Panamuwa II, probably around 732 BCE. The inscription, which is written in the Samʾalian language, summarizes Panamuwa II’s accession to the throne, his reign, and his achievements. Lines 2-6 of the inscription describe the disastrous situation of the kingdom during the reign of Panamuwa II’s predecessor, shortly before the kingdom became a vassal of Assyria. This section ends in line 6 with a description of high prices for basic commodities that were current in Samʾal/Yʾdy before Panamuwa II’s accession to the throne. Our interpretation of this line sheds new light on the economic situation by reading the inscription in the context of other ancient Near Eastern texts.